2019
DOI: 10.3390/s19051181
|View full text |Cite
|
Sign up to set email alerts
|

SynSys: A Synthetic Data Generation System for Healthcare Applications

Abstract: Creation of realistic synthetic behavior-based sensor data is an important aspect of testing machine learning techniques for healthcare applications. Many of the existing approaches for generating synthetic data are often limited in terms of complexity and realism. We introduce SynSys, a machine learning-based synthetic data generation method, to improve upon these limitations. We use this method to generate synthetic time series data that is composed of nested sequences using hidden Markov models and regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 18 publications
(18 reference statements)
0
87
0
1
Order By: Relevance
“…O trabalho gera regras de aprendizado com base nos atributos inseridos pelo usuário para construir relacionamentos entre esses atributos, e a técnica utilizada foi aárvore de decisão. Existem também trabalhos que produzem dados para problemas específicos, como (Dahmen and Cook 2019) que escreveram um artigo sobre o sistema de geração de dados para aplicativos de assistência médica, limitando a geração de novos dados apenas para esses casos.…”
Section: Trabalhos Relacionadosunclassified
“…O trabalho gera regras de aprendizado com base nos atributos inseridos pelo usuário para construir relacionamentos entre esses atributos, e a técnica utilizada foi aárvore de decisão. Existem também trabalhos que produzem dados para problemas específicos, como (Dahmen and Cook 2019) que escreveram um artigo sobre o sistema de geração de dados para aplicativos de assistência médica, limitando a geração de novos dados apenas para esses casos.…”
Section: Trabalhos Relacionadosunclassified
“…Krall et al [17], in turn, augmented electroencephalographic data using temporal and spatial or rotational distortions. The importance of time-series augmentation for healthcare applications was considered by Dahmen and Cook [18]. In that work, nested sequences obtained with hidden Markov models and regression models were used.…”
Section: Related Workmentioning
confidence: 99%
“…Analyzing the papers selected and summarized in Table S13, it can be observed that 78% of them exclusively analyze smart homes, 16% take into consideration smart buildings in general, 3% analyze both smart homes and buildings, while the remaining 3% of the selected papers refer to smart workplace environments. The authors of these scientific articles make use of different types of sensors in their analyses, including wireless sensor networks [70,115,[119][120][121][122][123][124]; passive infrared motion sensors [82,97,117,118,122,125,126]; motion sensors [25,70,81,118,120,127,128]; environmental sensors [10,25,81,82,[116][117][118]123,[127][128][129][130][131][132]; temperature sensors [116,118,120,123,125,[131][132][133]; humidity sensors…”
Section: Unsupervised Learningmentioning
confidence: 99%
“…The performance metrics that chosen by the authors of the scientific papers using the Hidden Markov Model integrated with sensor devices in smart buildings included: Accuracy [3,10,25,33,70,115,117,120,122,123,125,127,131,133,136,138]; Precision [25,118,128,133,135,137]; Recall [25,118,128,135]; F-Measure [25,81,121,130,133]; Sensitivity and Specificity [25,33,133]; F1 Score [116,133]; Confusion Matrix [116,127,129]; and Correctness [97,118]. In addition to the above-mentioned performance metrics, other methods that were used to assess the performance of the developed methods by the authors of the scientific papers selected and summarized in Table S13 included: a numerical case study highlighting the efficiency of the developed model [134]; thread latency [119]; evaluation of energy savings…”
Section: Unsupervised Learningmentioning
confidence: 99%
See 1 more Smart Citation